Method for producing eco-friendly zeolite using magma
Patent Information
- Application Number
- KR1020240177963
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2044-12-03
Smart Images

Figure 112024134073389-PAT00001
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing zeolite by recycling gangue generated during an effective mineral extraction process, and more specifically, to a method for manufacturing eco-friendly zeolite using improved gangue that enables mass production of zeolite by reducing calcium oxide, which hinders the crystallization of zeolite among the components of gangue crushed to a certain size, to a level below a certain threshold, mixing an alkaline substance in powder form and applying heat to fuse uniformly, and then mixing the fused powdered gangue mixture with water together with zeolite seeds and an aluminum-containing substance to ensure a quality above a certain level through synthesis and drying processes. Background Technology
[0003] After the ore undergoes a sorting process to obtain the target metal from the ore, the rock byproducts remaining after the ore is not industrially utilized are called tailings; among these, rocks that are discarded due to having almost no mineral content are called gangue.
[0004] In addition, it includes rocks discarded from coal mines in addition to mineral mines.
[0005] Although the overall deterioration of ore grade is a global phenomenon, the demand for mineral resources continues to rise. Consequently, the difficulty of recovering metals from low-grade ore persists, leading to an increase in the amount of discarded gangue; however, the reality is that it is being disposed of as simple waste due to mining byproducts.
[0006] In particular, due to environmental protection regulations, it is difficult to economically dispose of gangue generated during the mining process, resulting in large quantities of gangue being left abandoned in mining areas.
[0007] Although the composition of such gangue varies slightly depending on the mine in which it is mined, it generally consists of 40–65% SiO2, 5–35% Al2O3, 1–10% Fe2O3, and other components such as TiO2, CaO, and MgO. Among these components, silica and alumina are major components of zeolite, and zeolite can be synthesized using them. Zeolite can be synthesized using gangue from mining waste and recycled.
[0008] Although numerous patents have been presented for methods of manufacturing zeolites using waste, most of them relate to methods of manufacturing zeolites by recycling incineration ash generated from thermal power plants. However, due to the process characteristics of thermal power plants, the CaO content in the incineration ash remains high at 20% by weight or higher, making it difficult to synthesize zeolites in a form suitable for commercial application.
[0009] Conventional zeolite synthesis methods use strong alkaline solutions during the hydrothermal synthesis process, which presents problems such as reduced equipment durability due to the need for mass production of zeolites and equipment corrosion.
[0010] Furthermore, due to the characteristics of waste, the composition of gangue varies depending on the region where it is generated, making it difficult to mass-produce zeolites of uniform quality; therefore, research on new methods for zeolite synthesis is currently necessary.
[0011] As for related technology, Korean Patent No. 10-1602933 (registered on March 7, 2016; hereinafter referred to as 'Prior Art 1') presents a method for synthesizing zeolite using bottom material from a thermal power plant.
[0012] Prior art document 1 comprises the step of synthesizing zeolite by crushing bottom ash accumulated on the bottom of a boiler for a thermal power plant, removing a certain amount of CaO, fusing it at high temperature, and then mixing it with a NaOH or Na2CO3 solution and hydrothermally synthesizing it at 80°C to 100°C under atmospheric pressure conditions.
[0013] The aforementioned prior art document 1 synthesizes zeolites using strong alkaline substances and a hydrothermal synthesis method, which makes it somewhat unsuitable for mass production. Additionally, since CaO components, which are crystallization inhibitors, remain, there is a disadvantage in that it is difficult to synthesize various types of zeolites using the hydrothermal synthesis method under atmospheric pressure conditions due to the influence of crystallization inhibitors.
[0014] In addition, Korean Patent No. 10-1138854 (registered on April 16, 2012; hereinafter referred to as 'Prior Art 2') presented a zeolite synthesized from waste containing silica and alumina.
[0015] The aforementioned prior art document 2 describes a method for producing synthetic zeolite by mixing fly ash with an alkaline substance to fuse them, mixing water, an aluminum-containing substance, and a zeolite seed, and then aging and crystallizing the mixture.
[0016] However, the zeolite synthesized by the method of Prior Art 2 has a disadvantage of low crystallinity, such as zeolite types X and Y which have somewhat large pores, in addition to zeolite type A, because it contains a large amount of CaO, a substance that hinders crystallization depending on the characteristics of the waste material used as the raw material. Prior art literature
[0018] Korean Registered Patent No. 10-1602933 (Registered on March 7, 2016) Korean Registered Patent No. 10-1138854 (Registered on April 16, 2012) The problem to be solved
[0019] The present invention was created to solve the various problems of the aforementioned conventional technology, and its main purpose is to provide a method for manufacturing an eco-friendly zeolite using improved gangue that enables mass production of zeolite by reducing calcium oxide, which hinders the crystallization of zeolite among the components of gangue crushed to a certain size, to a level below a certain threshold, mixing an alkaline substance in powder form and applying heat to fuse it uniformly, and then mixing the fused powdered gangue mixture with water together with zeolite seeds and an aluminum-containing material to ensure a quality above a certain level through synthesis and drying processes. means of solving the problem
[0021] The present invention provides a method for manufacturing an eco-friendly zeolite using gangue, characterized by comprising: a first step of grinding gangue to 50 mesh or less as a means to achieve the above-mentioned purpose; a second step of removing CaO components that hinder the crystallization of the zeolite during the manufacture of synthetic zeolite; a third step of fusing the gangue powder by mixing it with an alkaline substance and heat-treating it; a fourth step of mixing the gangue mixture fused with the alkaline substance with water and mixing a material containing aluminum and a zeolite seed; a fifth step of aging the mixture; a sixth step of crystallizing the mixture; and a seventh step of producing the synthesized zeolite.
[0022] At this time, the gangue used in the first step is also characterized by being waste gangue discarded from mines.
[0023] In addition, in the second step above, the method is characterized by removing CaO components by adding a chemical additive, sodium silicate (Na2SiO3), in a range of 0.5 to 5 weight percent relative to the total weight of the gangue powder.
[0024] In addition, the method is characterized by selecting and using one or more of sodium hydroxide (NaOH), sodium carbonate (Na2CO3), and sodium silicate (Na2SiO3) as alkaline substances in the third step; mixing 30 to 300 parts by weight of the alkaline substance with 100 parts by weight of crushed powdered gangue powder; and heat treating at 500 to 900°C for 1 to 3 hours to fuse the gangue powder and the alkaline substance.
[0025] In addition, the above 5th and 6th steps may use an autoclave, a batch reactor, or a microwave reactor, and are characterized by having a synthesis time of 10 minutes to 12 hours at a temperature of 90 to 100°C.
[0026] In addition, it is characterized by transferring the wastewater generated during the filtration and washing process of each stage to the previous stage for recycling. Effects of the invention
[0028] According to the present invention, an improved effect can be obtained to enable mass production of zeolite by reducing calcium oxide, which hinders the crystallization of zeolite among the components of gangue crushed to a certain size, to a level below a certain threshold, mixing an alkaline substance in powder form and applying heat to fuse uniformly, and then mixing the fused powder gangue mixture with water together with zeolite seeds and an aluminum-containing substance, and ensuring a quality above a certain level through synthesis and drying processes. Specific details for implementing the invention
[0030] Before describing the present invention in more detail, the terms and words used in this specification and claims should not be limited to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept consistent with the technical spirit of the present invention, based on the principle that the concept of a term can be appropriately defined to best describe the invention.
[0031] The method for manufacturing an eco-friendly zeolite using gangue according to the present invention comprises: a first step of grinding gangue to 50 mesh or less; a second step of removing CaO components that hinder the crystallization of the zeolite during the manufacture of synthetic zeolite; a third step of fusing gangue powder by mixing it with an alkaline substance and heat-treating it; a fourth step of mixing the gangue mixture fused with the alkaline substance with water and mixing a material containing aluminum and a zeolite seed; a fifth step of aging the mixture; a sixth step of crystallizing the mixture; and a seventh step of producing the synthesized zeolite as a product.
[0032] At this time, the gangue used in the first step above can be crushed gangue, which is waste generated from various mines.
[0033] In order to remove the CaO component, which acts to hinder crystallization during the synthesis of zeolite, from the components of gangue, which is mainly in the form of rock, it is desirable to grind the gangue into a powder of 50 mesh or less.
[0034] In addition, the second step may include a first process of removing CaO components using hot water and a weak alkaline additive, a second process of dehydrating the gangue powder from which CaO components have been removed, and a third process of drying the gangue powder cake from which moisture has been removed by applying heat.
[0035] In this case, the first process can increase the crystallization rate of the synthetic zeolite by removing CaO typically contained in gangue at a level of 10 weight percent, and can enable the production of various types of synthetic zeolites.
[0036] Although it is advantageous to completely remove the above CaO component from the gangue powder to improve the crystallinity of the synthetic zeolite, it is desirable to reduce it to 3% by weight or less relative to the total weight of the gangue powder for economic reasons.
[0037] In addition, the first process described above is a process of immersing and stirring gangue powder in a hot water tank at 45 to 85°C for 1 to 3 hours to dissolve CaO components into the hot water, thereby reducing the CaO content remaining in the gangue powder to 3 weight% or less.
[0038] In addition, to increase the efficiency of leaching CaO components from gangue powder, compressed air is supplied into the stirrer while the gangue powder is immersed and stirred in a hot water tank, thereby increasing the removal efficiency through the increased stirring effect caused by fine air bubbles.
[0039] In particular, it is possible to use sodium silicate (Na2SiO3) as an additive to accelerate the leaching of CaO components, and it is preferable to add 0.5 to 5 weight percent relative to the total weight of gangue powder.
[0040] In this case, the added sodium silicate has the function of increasing the efficiency of removing residual CaO from gangue powder by adjusting the pH of the solution and acting as a buffer.
[0041] This provides the effect of lowering the CaO content of gangue powder to below a certain level and maintaining the quality of the final synthetic zeolite consistently.
[0042] In addition, the second process described above is a dehydration process for removing CaO leached into water along with water from gangue powder mixed with water that underwent the first process, and centrifugal separation or filter separation methods may be applied.
[0043] Next, a third process can be performed in which heat is applied to the moisture-removed gangue powder cake to dry it, thereby improving the efficiency of the subsequent process.
[0044] Meanwhile, the third step is a fusion step, and the alkaline material used in the third step is not particularly limited, but it is preferable to include a sodium component, and in particular sodium hydroxide (NaOH), sodium carbonate (Na2CO3), and sodium silicate (Na2SiO3) are preferred.
[0045] In addition, alkalis such as potassium hydroxide and potassium carbonate can be used, and it is preferable that the alkaline substances used be in a solid state.
[0046] The ratio of the alkali substance added in the third step above varies depending on the required component ratio of the zeolite, but it is preferably 30 to 300 parts by weight based on 100 parts by weight of gangue powder, and the heat treatment is preferably performed at a temperature of 500 to 900°C.
[0047] This is because high-temperature heat treatment causes gangue and alkaline substances to melt and fuse with each other, forming a structure favorable for zeolite synthesis.
[0048] In other words, through a high-temperature heat treatment fusion process, the main components of gangue are transformed into water-soluble Na2SiO3 or alkaline aqueous soluble NaAlSiO4, forming the aluminate and silicate ion sources necessary for zeolite synthesis.
[0049] This high-temperature heat treatment is usually carried out for about 1 to 3 hours.
[0050] Here, when the alkali substance is sodium hydroxide, it is preferable that the weight of sodium hydroxide is 100 to 130 parts by weight per 100 parts by weight of gangue powder, and the heat treatment temperature can be performed at a temperature of 500 to 600°C.
[0051] On the other hand, when the above alkali substance is used as sodium carbonate alone or as a mixture of sodium silicate and sodium carbonate, it is preferable that the weight of the sodium carbonate or the mixture of sodium carbonate and sodium silicate is 100 to 300 parts by weight per 100 parts by weight of the gangue powder, and it is preferable that the heat treatment of the fusion step be performed at a temperature of 800 to 900°C.
[0052] If a certain amount of sodium carbonate or a mixture of sodium carbonate and sodium silicate is mixed with gangue powder and heat-treated at a temperature of 800°C or lower to fuse, it is not desirable because the quartz or mullite contained in the gangue powder does not fuse and remains in its original state. It is preferable to heat-treat by heating to 800°C to 900°C so that the material fuses into a form of Na2SiO3, which is easy to use as a raw material for zeolite, or NaAlSiO4, which dissolves in an alkaline aqueous solution.
[0053] And, in the fourth step above, the fused gangue mixture is mixed with water and an aluminum-containing material and a zeolite seed is mixed. For every 100 parts by weight of the gangue fusion product made in the fusion step, 300 to 800 parts by weight of water, 1 to 30 parts by weight of the aluminum-containing material (depending on the composition ratio of the synthetic zeolite finally required and the chemical composition of the fused gangue powder), and 0.1 to 10 parts by weight of the zeolite seed are mixed.
[0054] If the above-mentioned water is mixed in an amount of less than 300 parts by weight, the alkali concentration becomes too high, increasing the production of Na-P1 or sodalite, which have relatively low utility, and if the amount of water exceeds 800 parts by weight, the crystallization rate of the zeolite slows down, making mass production difficult, so it is desirable to mix within the above range, and more preferably, to mix in an amount of 450 to 600 parts by weight.
[0055] In addition, the above aluminum-containing material is added to adjust the composition ratio of SiO2 / Al2O3 of the synthetic zeolite, and NaAlO2 can be used as such aluminum-containing material, and an aluminum-based waste coagulant (with an Al content of 5 to 40 weight%) can also be used, and other aluminum-based coagulants can also be used.
[0056] In addition, the above-mentioned zeolite seed serves as a template for the finally produced synthetic zeolite and plays a role in determining the shape of the manufactured synthetic zeolite. A preferred zeolite seed is coal ash.
[0057] And, the aging step, which is the fifth step, is a step in which the mixture of the fourth step is heated at a low temperature of 70°C or lower in a reactor while stirring to allow aging to occur, and a more preferable aging temperature is 20°C to 60°C.
[0058] Additionally, in the present invention, before performing the fourth step, a step of forming a stirred mixture may be further performed by adding 2.5 parts by weight of lithium-aluminosilicate (LAS), 4.0 parts by weight of modified nano-sulfur, 2.5 parts by weight of butylated hydroxytoluene, 5.0 parts by weight of metakaolin, 3.5 parts by weight of cera alba, and 4.5 parts by weight of tridymite to 100 parts by weight of the gangue mixture fused with an alkali substance after the third step, and stirring for 30 to 60 minutes.
[0059] This is intended to increase the reactivity of the gangue mixture and enhance the expression of characteristics during the fourth stage.
[0060] In this case, lithium aluminosilicate (LAS) enhances long-term strength development, shrinkage reduction, water resistance, chemical resistance, and freeze-thaw resistance.
[0061] In addition, modified nano-sulfur enhances crack resistance, chemical resistance, and especially chloride ion barrier properties.
[0062] In addition, butylated hydroxytoluene inhibits oxidation, stabilizes initial curing, and significantly enhances the inhibition of material bleeding.
[0063] In addition, the above metakaolin increases watertightness and durability.
[0064] In addition, Cera Alba ensures tensile strength through elastic cushioning.
[0065] In addition, Tridymite enhances water resistance, cushioning, and elastic recovery.
[0066] On the other hand, the fifth step is a step of stirring so that the gangue fusion containing the main components constituting the synthetic zeolite can be sufficiently dissolved / dispersed in water, and can be performed by stirring for 2 to 24 hours, preferably 5 to 20 hours, more preferably 12 to 14 hours.
[0067] At this time, if the aging time is less than 2 hours, the gangue fusion product is not sufficiently dissolved / dispersed in water, resulting in a smaller amount of zeolite synthesized in subsequent stages, and if the aging time exceeds 14 hours, the production volume of zeolite generated is not large relative to the increase in input time, so economic feasibility is lacking, so it is desirable to carry out aging within the above range.
[0068] In addition, the above-mentioned 6th step is a step of maintaining the reaction temperature of the mixture aged through the 5th step at 90 to 100°C to allow crystallization and growth of the synthetic zeolite.
[0069] The crystallization step is carried out by a hydrothermal reaction, and while such a hydrothermal reaction can usually be performed in an autoclave, the production of synthetic zeolite in the present invention can also be carried out in a general batch reactor.
[0070] This crystallization step can be performed for 2 to 12 hours, but more preferably for 3 to 6 hours.
[0071] In addition, a microwave reactor may be used for the crystallization step to shorten the reaction time, and the reaction time may be carried out in the range of 10 to 90 minutes.
[0072] When synthesizing zeolites in a microwave reactor, the crystallization reaction time of the zeolite can be made extremely short, and zeolites A, X, Y, etc. can be efficiently synthesized by optimizing the synthesis conditions of the zeolite to be synthesized.
[0073] In addition, the present invention can further improve the strength of the synthetic zeolite by separating the manufactured synthetic zeolite from water, filtering, washing, and drying it, and then calcining it at a certain temperature.
[0074] The drying of water contained in the synthetic zeolite can usually be performed at 90 to 110°C, and the subsequent calcination step can be performed at a temperature of 500 to 550°C.
[0075] In addition, the wastewater collected after filtration and washing can be reused as water for the second and fourth stages mentioned above, allowing for the recycling of wastewater generated during the process and thus reducing environmental pollution and manufacturing costs.
[0076] The synthetic zeolite produced by the above method can be used as a water treatment catalyst by supporting a divalent metal, and can be used for various purposes such as adsorbents for various heavy metals and metal ion chelating agents in detergents.
[0077] The following describes the embodiments.
[0078] After collecting waste gangue discarded from the mine, it was crushed into a powder of 50 mesh (approx. 300 µm) or less using a crusher, and the composition of the crushed gangue powder was analyzed by XRF and is shown in Table 1 below.
[0079] ingredient SiO2 Al2O3 CaO Fe2O3 TiO2 MgO ect total Content (wt%) 55.10 29.45 9.15 1.83 1.73 1.68 1.06 100
[0080] Next, gangue powder was placed in a stainless steel reactor and stirred in hot water at 80°C for 1 hour to reduce the CaO content to 7% by weight or less relative to the total weight of the gangue powder.
[0081] At this time, to accelerate the removal of CaO components, sodium silicate (Na2SiO3) was added to hot water, the moisture of the gangue powder with reduced CaO content was removed by a filter pressing method, and the recovered gangue powder cake was dried and supplied to the next fusion stage.
[0082] 120g of sodium hydroxide was mixed with 100g of the above gangue powder as an alkaline substance and maintained at a temperature of 550℃ for 1 hour to fuse into a substance that is easily soluble in water.
[0083] In the above fusion step, 100g of the fused gangue mixture, 500g of water, and 1.5g of zeolite 4A seed were introduced into a stainless steel reactor. At this time, since the molar ratio of SiO2 to Al2O3 among the components of the analyzed gangue was approximately 2.9, 10g of NaAlO2, selected as an aluminum-containing material, was additionally introduced to adjust the molar ratio of SiO2 to Al2O3 to 2.5.
[0084] Afterwards, an aging step was carried out by stirring the above mixture in a stainless steel reactor maintained at 40°C for 12 hours.
[0085] Then, the temperature of the aged mixture was raised to 100°C and stirred and reacted for 4 hours to grow crystallized and synthesized zeolite.
[0086] Synthetic zeolite, after crystallization and growth were completed, was washed with pure water and dehydrated, and then dried in a drying oven maintained at 100°C to produce synthetic zeolite in powder form.
[0087] [Example 1]
[0088] Synthetic zeolite was manufactured by the above manufacturing method, and the CaO content relative to the total weight of the gangue powder was controlled to 7% by weight by controlling the reaction time of the CaO removal step.
[0089] [Example 2]
[0090] Synthetic zeolite was manufactured by the above manufacturing method, and the CaO content relative to the total weight of the gangue powder was controlled to 5% by weight by controlling the reaction time of the CaO removal step.
[0091] [Example 3]
[0092] Synthetic zeolite was manufactured by the above manufacturing method, and the CaO content relative to the total weight of the gangue powder was controlled to 3% by adjusting the reaction time of the CaO removal step.
[0093] [Example 4]
[0094] Synthetic zeolite was manufactured by the above manufacturing method, and the CaO content relative to the total weight of the gangue powder was controlled to 1% by weight by controlling the reaction time of the CaO removal step.
[0095] [Example 5]
[0096] Synthetic zeolite was manufactured by the above manufacturing method, and the CaO content relative to the total weight of the gangue powder was controlled to 0.5% by weight or less by controlling the reaction time of the CaO removal step.
[0097] [Example 6]
[0098] Synthetic zeolite was manufactured by the above manufacturing method, and the CaO content relative to the total weight of the gangue powder was controlled to 1.0 wt% by controlling the reaction time of the CaO removal step and adding 1 wt% of sodium silicate (Na2SiO3).
[0099] [Example 7]
[0100] Synthetic zeolite was manufactured by the above manufacturing method, and the CaO content relative to the total weight of gangue powder was controlled to 0.5% by weight or less by controlling the reaction time of the CaO removal step and adding 1% by weight of sodium silicate (Na2SiO3).
[0101] [Comparative Example]
[0102] Synthetic zeolite was manufactured by the above manufacturing method, and since the CaO removal step was not performed, the CaO component contained in the gangue powder was not removed.
[0103] The chemical composition (%) and degree of crystallinity of synthetic zeolites prepared by recycling gangue measured by XRF (X-Ray Fluorescence) of the above examples, comparative examples, and commercial products are shown in Table 2.
[0104] Composition (wt%) Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Comparative example Commercial products (waco) SiO2 44.1 44.3 45.0 45.3 45.1 45.3 45.4 44.2 47.3 Al2O3 31.7 37.1 38.2 36.2 36.9 36.1 36.6 30.9 34.9 Na2O 12.5 12.6 12.6 12.5 12.6 12.8 12.8 9.1 17.7 CaO 6.9 5.1 3.0 1.1 0.5 1.0 0.4 9.5 0.05 Fe2O3 1.8 1.8 1.9 1.9 1.9 1.9 1.9 1.9 0.03 TiO2 1.5 1.5 1.5 1.5 1.5 1.5 1.5 1.6 - MgO 1.2 1.2 1.2 1.2 1.2 1.1 1.1 1.7 - ect 0.3 0.3 0.3 0.3 0.3 0.3 0.3 1.1 0.02 total 100 100 100 100 100 100 100 100 100 Crystallinity * (%) 72.3 76.1 86.1 90.5 92.3 91.1 93.5 68.8 100
[0105] At this time, the degree of crystallization is calculated as shown in the equation below.
[0106]
[0107] As shown in Table 2, the synthetic zeolite produced by the present invention contained some impurities such as CaO in addition to the basic chemical composition of zeolite, SiO2, Al2O3, and Na2O, but in the case of [Examples 4 to 7], the degree of crystallization was found to be not significantly different from that of pure zeolite and exhibited performance equivalent to that of commercial zeolite.
[0108] This is related to the removal rate of CaO present in the gangue, and achieving this means that the time of the CaO removal step in the second stage mentioned above is extended.
[0109] However, in order to increase the efficiency of the CaO removal step, the present invention pursued a chemical method of adding sodium silicate (Na2SiO3) in addition to a physical method, thereby increasing the CaO removal efficiency by more than twofold and producing an effective and economically viable synthetic zeolite.
[0110] As explained above, the present invention has the advantage of enabling mass production of zeolite by reducing calcium oxide, which hinders the crystallization of zeolite among the components of gangue crushed to a certain size, to a level below a certain threshold, mixing an alkaline substance in powder form and applying heat to fuse it uniformly, and then mixing the fused powder gangue mixture with water together with zeolite seeds and an aluminum-containing substance to ensure a quality above a certain level through synthesis and drying processes.
Claims
Claim 1 A method for manufacturing an eco-friendly zeolite using gangue, comprising: a first step of grinding gangue to 50 mesh or less; a second step of removing CaO components that hinder the crystallization of the zeolite during the manufacture of synthetic zeolite; a third step of fusing the gangue powder by mixing it with an alkaline substance and heat-treating it; a fourth step of mixing the gangue mixture fused with the alkaline substance with water and mixing it with a material containing aluminum and a zeolite seed; a fifth step of aging the mixture; a sixth step of crystallizing the mixture; and a seventh step of commercializing the synthesized zeolite; wherein the gangue used in the first step is waste gangue discarded from a mine; and wherein, in the second step, sodium silicate (Na2SiO3), a chemical additive, is added in a range of 0.5 to 5 weight percent relative to the total weight of the gangue powder to remove CaO components. Claim 2 delete Claim 3 delete Claim 4 A method for manufacturing an eco-friendly zeolite using gangue according to claim 1, characterized in that, in the third step, one or more alkaline substances selected from sodium hydroxide (NaOH), sodium carbonate (Na2CO3), and sodium silicate (Na2SiO3) are used; 30 to 300 parts by weight of the alkaline substance are mixed with 100 parts by weight of crushed powdered gangue; and heat-treat at 500 to 900°C for 1 to 3 hours to fuse the gangue powder and the alkaline substance. Claim 5 A method for producing an eco-friendly zeolite using gangue according to claim 1, wherein the 5th and 6th steps may use an autoclave, a batch reactor, or a microwave reactor, and have a synthesis time of 10 minutes to 12 hours at a temperature of 90 to 100°C. Claim 6 A method for manufacturing eco-friendly zeolite using gangue, characterized in that, in claim 1, wastewater generated during the filtration and washing process of each stage is transferred to the previous stage for recycling.
Citation Information
Patent Citations
Preparation method of catalysis material containing Y type molecular sieve
CN101767026A
Method for preparing analcime from silicon-aluminum tailings
CN115818659A
SAPO-20 / MCM-48 zeolite soil passivator as well as preparation method and application thereof
CN118387893A
Synthetic Zeolite synthesized from Waste including Silica and Alumina
KR1020110022454A
Method for Manufacturing Synthetic Zeolites using Gangue
KR101602926B1
